KEEFEKTIVAN PENGGUNAAN MODEL DISCOVERY LEARNING DALAM PEMBELAJARAN MENULIS TEKS CERPEN PADA SISWA SMP - Wasi’ah, Durotul; Nurlatifah, Ayu Siti; Firmansyah, Dida (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This research is based on the curiosity of the researchers in the use of the Discovery Learning model for learning to write short story texts in class IX A Cipongkor 2 Junior High School. Based on the background of the research, the researcher can formulate a problem, namely 1) Is the Discovery Learning model effective in learning to write short story texts? and 2) What is the description of student performance during the implementation of learning with the Discovery Learning model? And so the researcher aims to find out the implementation of the discovery learning model in writing short text students of class IX A of Cipongkor Junior High School 2 with an object of 30 students as samples. The method used was quasi-experiment in the form of One Group Pretest and Posttest Design. Data were analyzed by descriptive analysis using the initial and final tests. The criteria used are the suitability of the theme, the element of building short stories and linguistic rules. Based on the results of data verification there was a significant increase between the results of the initial test which amounted to 47% to 74% in the final test. Then it can be concluded that the Discovery Learning model is effectively used.